2014
DOI: 10.1371/journal.pone.0088576
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Vestibular Loss Impairs External Space Representation

Abstract: The vestibular system is responsible for a wide range of postural and oculomotor functions and maintains an internal, updated representation of the position and movement of the head in space. In this study, we assessed whether unilateral vestibular loss affects external space representation. Patients with Menière's disease and healthy participants were instructed to point to memorized targets in near (peripersonal) and far (extrapersonal) spaces in the absence or presence of a visual background. These individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
1
10
0
1
Order By: Relevance
“…Likewise neurological patients with a spatial hemineglect, which involves the vestibular cortex, have both object-based allocentric and body-centered egocentric impairment of spatial awareness [5]. Similar findings were seen in patients after an acute unilateral vestibular loss [6].…”
Section: Dear Sirsmentioning
confidence: 52%
“…Likewise neurological patients with a spatial hemineglect, which involves the vestibular cortex, have both object-based allocentric and body-centered egocentric impairment of spatial awareness [5]. Similar findings were seen in patients after an acute unilateral vestibular loss [6].…”
Section: Dear Sirsmentioning
confidence: 52%
“…A second explanation is that spatial perception (or navigational abilities) might be truly altered in patients with vestibular disorders [22,24,[63][64][65], but that the impairment could be rapidly compensated, or reduced through vestibular rehabilitation [66]. Furthermore, spatial perception may be more difficult to self-evaluate because of the temporary characteristic of their affection in vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…By regulating the skeletal muscle tone, the central vestibular system pathways, mainly the lateral vestibulospinal tract, play an important role in the correct postural muscle activity and maintaining correct body posture [6][7][8][9]. The vestibulospinal tract which is the neural tract starting primarily in lateral vestibular nucleus, partly in the inferior vestibular nucleus and the medial vestibular nucleus runs in front of and ends in the anterior part of the spinal cord where motor representation is located [7,33].…”
Section: Discussionmentioning
confidence: 99%
“…The sensory processes (vision, tactile, vestibular system), movement and body image are integrated for controlling overall body posture and spinal alignment The integration of external, proprioceptive and interoceptive stimuli generate in the central nervous system, a coherent picture of the various parts of the body, the body as a whole and the body's interaction to the environment [6][7][8][9]. In recent years, there has been an increasing interest in the role of vestibular system on controlling the body posture [7][8][9]. According to imaging studies by Pfeiffer et al, cortex activity during vestibular stimulation, identified in complex regions of cerebral cortex, coincides with cortical representation for vision, movement, somatosensation, and proprioception [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation